2023
DOI: 10.1002/adhm.202300118
|View full text |Cite
|
Sign up to set email alerts
|

Multistage‐Responsive Dual‐Enzyme Nanocascades for Synergistic Radiosensitization‐Starvation Cancer Therapy

Abstract: Radiotherapy is a common cancer treatment approach in clinical practice, yet its efficacy has been restricted by tumor hypoxia. Nanomaterials‐mediated systemic delivery of glucose oxidase (GOx) and catalase (CAT) or CAT‐like nanoenzymes holds the potential to enhance tumor oxygenation. However, they face the challenge of intermediate (hydrogen peroxide [H2O2]) escape during systemic circulation if the enzyme pair is not closely placed to largely decompose H2O2, leading to oxidative stress on normal tissues. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The dual-enzyme cascade system of GOx and CAT has been extensively investigated for tumor therapy. , In this approach, GOx converted glucose into gluconic acid and toxic hydrogen peroxide (H 2 O 2 ), which could be rapidly converted into H 2 O and oxygen (O 2 ) by CAT in situ , resulting in rapid glucose depletion (Figure e). The catalytic effect is the basis for enzymatic oncotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The dual-enzyme cascade system of GOx and CAT has been extensively investigated for tumor therapy. , In this approach, GOx converted glucose into gluconic acid and toxic hydrogen peroxide (H 2 O 2 ), which could be rapidly converted into H 2 O and oxygen (O 2 ) by CAT in situ , resulting in rapid glucose depletion (Figure e). The catalytic effect is the basis for enzymatic oncotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…10,182 To overcome this bottleneck, numerous nanozymes based on transition metals containing high atomic number (Z) elements have been developed as radiosensitizers to augment tumor responses to radiation and enhance treatment efficacy. 185,186 These nanozymes not only alleviate hypoxia through CAT-like activity but also generate abundant ROS via Auger and photoelectrons emitted from their high-Z metal elements under X-ray irradiation to induce DNA damages. 187,188 For example, Choi et al developed the synthesis of mPEG-conjugated porous platinum nanoparticles (PtNPs) with exceptional CAT-like activity and a high-Z Pt element, which served as a radiosensitizer to enhance RT in vivo (Figure 17A).…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…X-ray therapy, also known as radiotherapy (RT), is a widely employed clinical modality for cancer treatment, characterized by the induction of ROS and DNA damage through X-ray irradiation to effectively eliminate malignant cells. However, the treatment of cancer with RT alone often presents a significant challenge due to the development of radioresistance caused by DNA damage repair mechanisms and hypoxia. , To overcome this bottleneck, numerous nanozymes based on transition metals containing high atomic number ( Z ) elements have been developed as radiosensitizers to augment tumor responses to radiation and enhance treatment efficacy. , These nanozymes not only alleviate hypoxia through CAT-like activity but also generate abundant ROS via Auger and photoelectrons emitted from their high- Z metal elements under X-ray irradiation to induce DNA damages. , For example, Choi et al developed the synthesis of mPEG-conjugated porous platinum nanoparticles (PtNPs) with exceptional CAT-like activity and a high- Z Pt element, which served as a radiosensitizer to enhance RT in vivo (Figure A) . The results from the O 2 generation experiment demonstrated that PtNPs efficiently converted H 2 O 2 into O 2 , highlighting their nanozyme properties resembling CAT.…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…Taking glucose as an example, cancer cells proliferate faster compared to normal cells, which leads to accelerated glucose metabolism through glycolysis, and the consumption of glucose as a metabolic substrate increases; if the supply of glucose is reduced at this time, the cancer cells will be “starved to death” due to the lack of nutrients, which is a strategy known as “starvation therapy”. , Glucose oxidase-mediated starvation therapy (GST) is widely used in tumor therapy because of its low side effects and remarkable effectiveness. , However, the enzyme produces excess H 2 O 2 while oxidizing glucose, causing irreversible damage to normal cells. , The above shortcomings limit the further development of glucose oxidase in tumor therapy. Fortunately, a cascade of enzymes composed of glucose oxidase (GOX) and horseradish peroxidase (HRP) could smoothly eliminate the H 2 O 2 generated in the reaction, and the O 2 produced also alleviate the hypoxic state of the TME. , The cascade will further promote the glucose consumption of tumor cells, making the reaction cycle like a motor and accelerating the rate of glycolysis. …”
Section: Introductionmentioning
confidence: 99%